Technological and nutritional characterization of wheat breads added with eggplant flour: dependence on the level of flour and the size of fruit - Valerga, Lucia (2019)
Eggplant (Solanum melongena L.) is the third solanaceous of horticultural importance in the world, after potato and tomato. In the agricultural production of this vegetable, there are post-harvest losses and waste generation. Reduction of these inconveniences can be avoided by obtaining ingredients with high nutritional value for food processing, as breadmaking. Changes in wheat dough and bread quality due to the incorporation of eggplant flour were studied. Different levels (5, 7.5, 10%) of replacement with flour from Large eggplant were analysed. The optimum level of eggplant flour (7.5%) was used for comparison technological performance of eggplant?wheat breads elaborated with flour from eggplants of different size: small size eggplant (Baby, BE) and large size eggplant (Large, LE). Dough was characterized through farinographic (water absorption, development time, stability, softening degree) and fermentation parameters (maximum volume of fermented dough, fermentation time). Technological quality (specific volume, hardness, elasticity, number of crumb alveolus, colour of crust and crumb) and sensory analysis of breads were evaluated. Proximal composition and antioxidant activity of flour and breads were studied. Water absorption, development time and softening degree increased, while bread volume, elasticity and the area occupied by alveoli decreased with the presence of eggplant flour. Breads also became darker. Breads with 7.5% of BE, presented a harder crumb with lower luminosity than those with LE. Both type of breads were well accepted by consumers; nevertheless, BE was the bread that contains higher amount of compounds with antioxidant activity and therefore it is recommended for formulation of functional breads.